A real-time program trace compressor utilizing double move-to-front method - Uzelac, Vladimir; Milenkovic, Aleksandar (2009 46th ACM/IEEE Design Automation Conference, 2009)
This paper introduces a new unobtrusive and cost-effective method for the capture and compression of program execution traces in real-time, which is based on a double move-to-front transformation. We explore its effectiveness and describe a cost-effective hardware implementation. The proposed trace compressor requires only 0.12 bits per instruction of trace port bandwidth, at the cost of 25K gates.